Development of Online Biology Learning Media on Genetic Substance and Cell Division Material for Third Grade (XII) Methodist High School El Shadday Perbaungan - Maria Meita Simanjuntak; Syahmi Edi; Binari Manurung (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
The objectives of this study were as follows: (1) To develop online learning media products on Genetic Substance and Cell Division through feasibility and validity tests by material and media experts certifying that this biology learning media is suitable for use in the field; and (2) To determine whether or not the utilization of online learning media influences student learning outcomes through more active and comprehensive engagement, as determined by data analysis following the execution of the learning process. The learning outcomes of students are influenced by the level of effectiveness of online learning media pertaining to Genetic Substance and Cell Division, as measured by the Gain Score. The field trial successfully fulfilled the effectiveness criteria; therefore, it can be inferred that the developed online biology learning media pertaining to Genetic Substance and Cell Division has been utilized effectively and has the potential to enhance the academic performance of high school students in this subject matter. The research methodology is in accordance with Borg and Gall 's 4-D model, which comprises the following stages: determination or definition, design, development, and dissemination